Tak Ada Domba di Kampung Naga: Studi Etnografi Perayaan Idul Adha dan Hajat Sasih di Kampung Naga Tasikmalaya Jawa Barat - Rahman Rahman (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2015)
Human beings always try to implement their religious faith invarious rituals as an instrument to be closed to God. One of such rituals is‘Īd al-Aḍḥā (Islamic Great Bairam) conducted by the community KampungNaga.This ritual accomplishment is continued by Hajat Sasih as thanksexpression to their ancestors. However, they more respect their traditionalcustom, Hajat Sasih ritual, rather than Islamic ritual eventhough theyare actually Muslims. For this reason then they do not sacrifice a lamb inthe Great Bairam day (as obliged by the Islamic doctrine), for they claimthat they are poor people, but on the other occasion they do so for theirtraditional ritual such as ngaruwat lembur. This article uses ethno-sciencebelonging to James P. Spradley.